CRIMINAL LAW AND CRIMINOLOGICAL ASPECTS OF ARBITRARINESS - Kurbanova Xushvaqt Ashurovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with topical problems of theory and practice of criminal liability for self-law in the Criminal Code of the Republic of Uzbekistan, and criminal and criminological aspects of arbitrariness, analyzing the theoretical views and legislation of legal scholars. At the same time, sound, constructive proposals for the prevention of the crime of self-law have been put forward.